KAJIAN ASPEK EKONOMI DAN KETIMPANGAN WILAYAH PERKOTAAN SURAKARTA - Ratika Tulus Wahyuhana; Adnan A. Akbar Botanri (Program Studi Perencanaan Wilayah dan Kota Universitas Pasundan, 2017)
The measure of the success of development can be seen from the economic growth and the smaller income inequality among the population, between regions and between sectors. In fact, economic growth is not always followed by adequate equity. This condition occurs in the urban areas of Surakarta with rapid economic growth and developments that have exceeded administrative boundaries. Thus, the Research Question is: